Evaluating the influence of music at different sound pressure levels on medical students’ performance of standardized laparoscopic box training exercises - Nees, Lisa Katharina; Grozinger, Philipp; Orthmann, Natalie; Deutsch, Thomas M.; Hennigs, André; Domschke, Christoph; Wallwiener, Markus; Rom, Joachim; Riedel, Fabian (BMC medical education, 2021)
The influence of music on the performance of surgical procedures such as laparoscopy is controversial and methodologically difficult to quantify. Here, outcome measurements using laparoscopic box training tools under standardized conditions might offer a feasible approach. To date, the effect of music exposure at different sound pressure levels (SPL) on outcome has not been evaluated systematically for laparoscopic novices.
Gesehen am 07.06.2021